2008
DOI: 10.1186/1471-2229-8-62
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm (Elaeis guineensisJacq.) tissue culture ESTs: Identifying genes associated with callogenesis and embryogenesis

Abstract: Background Oil palm ( Elaeis guineensis Jacq.) is one of the most important oil bearing crops in the world. However, genetic improvement of oil palm through conventional breeding is extremely slow and costly, as the breeding cycle can take up to 10 years. This has brought about interest in vegetative propagation of oil palm. Since the introduction of oil palm tissue culture in the 1970s, clonal propagation has proven to be useful, not only in producing uniform planting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 70 publications
6
83
1
7
Order By: Relevance
“…A total of 19,471 embryogenesis related ESTs were obtained from Low et al (2008) and Lin et al (2009). The ESTs libraries were assembled using CAP3 program resulting to 13,020 sequences of contigs and singletons (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 19,471 embryogenesis related ESTs were obtained from Low et al (2008) and Lin et al (2009). The ESTs libraries were assembled using CAP3 program resulting to 13,020 sequences of contigs and singletons (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Target genes were derived from Expressed Sequence Tags (ESTs) from Low et al (2008), and Lin et al (2009) which were deposited in GenBank database EY396120-EY413718 and GH635901-GH637767. ESTs were subsequently assembled using CAP3 program (Huang & Madan 1999).…”
Section: In Silico Selection Of Snps Markermentioning
confidence: 99%
“…Expressed sequence tags (ESTs) have been developed from many monocot plant species including P. equestris , ginger (Chandasekar et al, 2009), oil palm (Low et al, 2008), wheat (Zhang et al, 2004) and maize (Fernandes et al, 2002). To date, more than 1700 floral fragrance compounds have been identified through biochemical analysis with the majority identified from higher plants whilst others are from animals, insects, marine organisms, algae and bacteria.…”
Section: Discovery Of Fragrance-related Genes From Vmpestsmentioning
confidence: 99%
“…(Elaeis guineensis) (Low et al, 2008;Singh et al, 2013). The ADH enzyme is essential for anaerobic metabolism (Dolferus et al, 1994;Dolferus et al, 1997), found in plants and prokaryotes, its activity is required for lignin biosynthesis and apparently also for defense-related functions (Umezawa, 2010).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%